Diagnostic Clues to Ectopic Pregnancy - Jahan Ara Saeed , Idowu Ghani, (Journal of Rawalpindi Medical College, 2013)
Background: To study the various diagnostic criteria used for ectopic pregnancy. Methods: This descriptive study included seventy patients diagnosed as ectopic pregnancy. Clinical presentations and physical findings were recorded. Urine pregnancy test, serum β hCG and abdominal ultrasound were the main diagnostic modalities. Findings at laparoscopy and laparotomy were analyzed. Results: Majority of the women presented with abdominal pain (90%) and amenorrhea (97.14%).Majority(82.84%) had an amenorrhea ranging from 4 weeks or less to 8 weeks. Cervical excitation was positive in 64.28% and adenexal mass was palpable in 15.7%. Urine pregnancy test and serum β hCG were positive in 82.8% and 95.2%. , respectively. Findings suggestive of ectopic were found in 81.42% on transabdominal ultrasound exam. Twenty five patients (35.6%) underwent diagnostic laparoscopy while 98.5% underwent laparotomy. Conclusion: Availability of sensitive and specific radio-immunoassays of β-human chorionic gonadotrophin (β-hCG) and high resolution transvaginal ultrasound (TVS) allows early detection of ectopic pregnancies